Development of Physics Teaching Materials Containing Local Wisdom to Train Students Critical Thinking Skills - Siti Mahmudah; Abdul Salam M; Dewi Dewantara (Universitas Lambung Mangkurat, 2023)
This study aimed to describe the feasibility of physics teaching materials containing local wisdom to train students' critical thinking skills. This study aims to describe the validity, practicality, and effectiveness of teaching materials and the achievement of critical thinking skills. This type of research is called research and development. The development model used for this is the ADDIE which consists of 5 stages: analysis, design, development, implementation, and evaluation. Data collection techniques include validation tests, student response questionnaires, and critical thinking skills assessments. The results obtained: 1) validity of teaching materials get 4,29 in the very good category, lesson plans with an average of 4,14 in the good category, student worksheets with an average of 4,27 in the very good category, and study result test with an average of 4, 26 categorized as very good; 2) the practicality of teaching materials with an average of 3,93 in the good category; 3) the effectiveness of teaching materials meets the criteria for completeness in the good category; 4) critical thinking skills through a high category learning outcome test. Therefore, electronic teaching materials containing local wisdom to train critical thinking skills are suitable for use in learning.